Reconceptualizing Dreamwork (With Apologies yo Lewis Carroll’s "Alice") as a Facet of Motherwork - Nelson, Adie; Nelson, Veronica B. (Qualitative Sociology Review, 2010)
While acknowledging some of the myriad ways in which the term "dreamwork" has been used by scholars over the past century, this article directs especial attention to dreamwork as both a facet of motherwork and form of anticipatory socialization. This particular conception views dreamwork as an interpersonal accomplishment and emphasizes its collaborative character. In arguing for its utility, we note how this conception of dreamwork complements insights found in other works and suggest how these ideas might be related, and future research on parental involvement in the lives of children strengthened, by gathering them together under the concept of dreamwork.